2006
DOI: 10.1002/cncr.21951
|View full text |Cite
|
Sign up to set email alerts
|

Mononuclear cell infiltration in clear‐cell renal cell carcinoma independently predicts patient survival

Abstract: BACKGROUND The impact of mononuclear cell infiltration on renal cell carcinoma (RCC) biology has been controversial, previously reported to be associated with either a favorable or unfavorable prognosis. The objective of the current study was to evaluate associations between mononuclear cell infiltration in routinely prepared paraffin‐embedded specimens with survival in patients with clear‐cell RCC. METHODS A total of 306 patients were identified treated with nephrectomy for clear‐cell RCC between 1990 and 199… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

4
60
0

Year Published

2006
2006
2021
2021

Publication Types

Select...
6
2

Relationship

2
6

Authors

Journals

citations
Cited by 73 publications
(64 citation statements)
references
References 31 publications
4
60
0
Order By: Relevance
“…In contrast, proximal tubules of the kidney, from which clear cell RCC tumors originate, were devoid of B7-H4 staining (22)(23)(24). Tumor B7-H4 expression was also associated with lymphocytic infiltration, which portends a poorer clinical outcome for patients with RCC (25). In addition, we observed that B7-H4 is associated with an increased risk of death from RCC and a higher risk for disease progression in patients with pathologically localized renal tumors in univariate analysis.…”
Section: Discussionmentioning
confidence: 99%
“…In contrast, proximal tubules of the kidney, from which clear cell RCC tumors originate, were devoid of B7-H4 staining (22)(23)(24). Tumor B7-H4 expression was also associated with lymphocytic infiltration, which portends a poorer clinical outcome for patients with RCC (25). In addition, we observed that B7-H4 is associated with an increased risk of death from RCC and a higher risk for disease progression in patients with pathologically localized renal tumors in univariate analysis.…”
Section: Discussionmentioning
confidence: 99%
“…However, a high infiltration rate of lymphocytes in RCC, particularly the clear cell type, is not correlated with a better clinical outcome, 28,29 whereas T cell infiltration is positively correlated with good prognosis in other tumors e.g., colon carcinoma. 26,27 This may indicate that tumor immune escape mechanisms may play an important role in RCC (reviewed in 31 ).…”
Section: Tumor Immunologymentioning
confidence: 95%
“…24,25 Therefore, in contrast to colon carcinoma and other solid tumors exhibiting a positive correlation between the numbers of tumor infiltrating lymphocytes and prognosis 26,27 no clear correlation was observed in RCC patients. 28,29 Furthermore, van den Hove and coauthors showed that tumor infiltrating CD8 þ T cells are highly activated, but functionally impaired. 30 These data indicate the presence of immune escape mechanisms in RCC that contribute to the failure of the immune system to control RCC growth (reviewed in 31 ).…”
mentioning
confidence: 99%
“…Several groups have reported that the presence of infiltrating mononuclear cells, including intratumor CD4 ϩ T cells, paradoxically, identifies patients with a poor prognosis (8,9). This observation suggests that a subset of tumor-infiltrating CD4 ϩ T cells may impede antitumor T and NK cell function (10).…”
Section: Targeting Molecular and Cellular Inhibitory Mechanisms For Imentioning
confidence: 99%